STRATEGI KEPEMIMPINAN EFEKTIF UNTUK MENINGKATKAN KINERJA TIM - Saleh, Munandi; Insani, Suci Mutiara; Herdiana Putra, Elang Langsa; Feriyanto, Feriyanto; Lestari, Tsani (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
Research on transformational and transactional leadership to improve team performance has been done by many previous researchers, but it is still rare to conduct research with loci in the field of hotels. The purpose of this study is to find out and explain effective leadership strategies to improve team performance. The research method used was quantitative descriptive, while as a sample, all Sukasantai Farmstay Sukabumi hotel employees totaled 50 respondents. The data collection method uses a questionnaire through Google Forms distributed to respondents. The results of the study stated that transformational and transactional leadership had a positive and significant influence on team performance, with an influence of 76.1% while other variables influenced 23.9%.